Radiopacity evaluation of new root canal filling materials by digitalization of images - Tanomaru-Filho, Mario; Jorge, Erica Gouveia; Guerreiro Tanomaru, Juliane Maria; Gonçalves, Marcelo [UNESP] (Elsevier B.V., 2007)
The aim of this study was to evaluate the radiopacity of five root canal filling materials (AH Plus, Intrafill, Roeko Seal, Epiphany, and EndoRez). Following the International Organization of Standardization 687612001, five circular specimens (10 X 1 mm) were made from each material. After the material set, radiographs were made using occlusal film and a graduated aluminum step-wedge varying in thickness from 2 to 16 mm. The dental X-ray unit (GE1000) was set at 50 Kvp, 10 mA, 18 pulses/second, and distance of 33.5 cm. The radiographs were digitized, and the radiopacity was compared with the aluminum step-wedge, using WIXWIN-2000 software (Gendex). Data (mm Al) were analyzed using ANOVA and Tukey tests. AH Plus and Epiphany were the most radiopaque materials (9.8 and 8.8 mm Al, respectively), followed by EndoRez (7.2 mm Al). Roeko Seal and Intrafill presented the lowest radiopacity values (5.7 and 6.1 mm Al, respectively). Although the materials evaluated demonstrated different radiopacities, all had values above the minimum recommended by the international Organization of Standardization.
Keywords: radiology; radiopacity; root canal filling materials